Consociation and the Resolution of Aboriginal Political Rights: The Example of the Northwest Territories, Canada - Asch, Michael (Culture, 1990)
Canada is in a period of high constitutional attention. As the review of our constitution takes place, issues concerning the relationship between aboriginal nations and other Canadians comes to the fore. In this paper, I address one of these issues: the translation of accepting the notion of “foundingness” with respect to the political rights of aboriginal nations into political reality. The core of my contribution details the issues and processes by which such a reality can be addressed. In addressing this theme, I focus on developments in the western part of the Northwest Territories where work, including preliminary negotiations between Native and non-Native northerners, has been already undertaken on this issue.